1979
DOI: 10.1002/ajmg.1320030304
|View full text |Cite
|
Sign up to set email alerts
|

The Neu‐Laxova syndrome—a distinct entity

Abstract: We report a stillborn girl with a complex syndrome of microcephaly, lissencephaly, severe subcutaneous edema, atrophic muscles, camptodactyly, syndactyly of toes and fingers, hypoplastic genitalia, and numerous structural changes of the brain and eyes. Similar cases have been reported by Neu et al [1], Laxova et al [2] and Povysilova et al [3]. The above-mentioned syndrome complex is a distinct genetic syndrome, for which we propose the eponym "the Neu-Laxova syndrome." Affected patients resemble each other st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 2 publications
1
35
0
Order By: Relevance
“…However, in agreement with other investigators [Lazjuk et al, 1979;Winter et al, 19811, we included them because of the many important similarities to the other patients with this syndrome. One of the major defects is lack of development of the brain.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, in agreement with other investigators [Lazjuk et al, 1979;Winter et al, 19811, we included them because of the many important similarities to the other patients with this syndrome. One of the major defects is lack of development of the brain.…”
Section: Discussionsupporting
confidence: 63%
“…Only ten infants with the Neu-Laxova syndrome have been described [Neu et al, 1971;Laxova et al, 1972;Polvj%ilovB et al, 1976;Lazjuk et al, 1979;Winter et al, 19811. Polvgsilova et a1 [I9761 thought that their three infants probably did not …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several syndromes share microcephaly and limb anomalies, (for instance the craniosynostosis-radial aplasia syndrome [ 11 , the SC phocomelia syndrome [ 2 ] , the Neu-Laxova syndrome [3], but the present condition seems quite distinct with intrauterine growth retardation and microcephaly so severe as to be incompatible with life.…”
Section: Discussionmentioning
confidence: 99%
“…Although abnormalities of the external genitalia have been reported [Neu et al, 1971;Povysilova et al, 1976;Lazjuk et al, 1979;Seemanova et al, 19851, hypoplastic ovaries have not previously been reported and cannot be explained.…”
Section: Pathologymentioning
confidence: 87%